(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The place and the role of a category of health in the Belarusian phraseology are firstly defined in this article. Due to culturological analysis of phraseological units various means, methods, estimation, characteristics, standards and stereotypes in perception of health are established in such opposites as – health, a healthy person – disposition, disease, an unhealthy person.